TINGKAT KESEJAHTERAAN KELUARGA PETANI NANAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Fira Novianingsih; Khairani khairani (JURNAL BUANA, 2022)
This study aims to determine the level of welfare of pineapple farmer families in Kualu Nenas Village, Tambang District, Kampar Regency. This type of research used in this research is descriptive research with a quantitative approach. The population in this study were all pineapple farmers totaling 390 people in 2020. With a total sample size of 80. The sampling technique method was incidental sampling. The results of this study show that the average income of 80 respondents is Rp. 2,269,063 and when compared with the national average poverty line of Rp. 1,990,170, the pineapple farming family in Kualu Nenas Village. are in the welfare category or are above the poverty line. Then food consumption is IDR 733,913 or 50.40% and non-food consumption is IDR 722,083 or 49.60%. Means the expenditure of Rp. 1,455,994. The calculation results of the GSR (Good Service Ratio) calculation show that pineapple farmers in Kualu Nenas Village, Tambang District, Kampar Regency are prosperous. Because the ratio of food expenditure and non-food expenditure is equal to 1.